Predicting Factors for High-Grade Cervical Dysplasia in Women With Low-Grade Cervical Cytology and Nonvisible Squamocolumnar Junction. (January 2019) - Bogani, Giorgio; Taverna, Francesca; Lombardo, Claudia; Ditto, Antonino; Martinelli, Fabio; Signorelli, Mauro; Chiappa, Valentina; Maggiore, Umberto Leone Roberti; Mosca, Lavinia; Sabatucci, Ilaria; Scaffa, Cono; Lorusso, Domenica; et al.
Objective: To assess the risk of developing high-grade cervical dysplasia among women with low-grade cervical cytology and nonvisible squamocolumnar junction (SCJ) at colposcopic examination. Methods: Data of consecutive women with low-grade intraepithelial lesion(≤LSIL) undergoing colposcopic examination, which was unsatisfactory (due to the lack of the visualization of the entire SCJ), were retrospectively reviewed. The risk of developing high-grade cervical intraepithelial neoplasia (CIN2+) was assessed using Kaplan-Meier and Cox models. Results: Data of 86 women were retrieved. Mean (standard deviation [SD]) age was 36.3 (13.4) years. A total of 71 (82.5%) patients had high-risk human papillomavirus (HR-HPV) at the time of diagnosis. Among the 63 patients undergoing repetition of HPV testing, 15 (24%) and 48 (76%) women had positive and negative tests for HR-HPV at 12 months, respectively. We observed that 5 (33%) of 15 patients with HPV persistence developed CIN2+, while only 1 (2%) patient of 48 patients without HPV persistence developed CIN2+ (odds ratio [OR]: 23.5; 95% confidence interval [CI]: 2.46-223.7; P < .001). The length of HR-HPV persistence correlated with an increased risk of developing CIN2+ ( P < .001; P for trend). High-risk HPV persistence is the only factor predicting for CIN2+ (hazard ratio: 3.19; 95% CI: 1.55-6.57; P = .002). Conclusions: High-risk HPV persistence predicts the risk of developing CIN2+ in patients with unsatisfactory colposcopic examination. Further studies are warranted in order to implement the use of HPV testing in patients with unsatisfactory colposcopy.